Analisis Hubungan Biaya Overhead Pabrik Terhadap Biaya Lain Pada PT. Insan Citraprima Sejahtera - Hariyanti Hariyanti (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Welcoming free trade, competition in the business world is getting tougher. As many companies emerge, according to the law of Supply and Demand, competition will arise between similar and dissimilar industries to dominate the market using various methods and strategies. When these companies or industries are established, they certainly have a goal to be achieved. Of the many goals that a company wants to achieve, it is to gain profit or profit. The author's anxiety in facing increasingly tough competition makes the author try to examine whether the calculation of overhead costs is in accordance with the accounting process implemented, because companies are required to be able to make decisions quickly and precisely, because being careful in making decisions will affect the continuity and development of the company, wrong One decision that must be taken in the management of a company is decisions and policies regarding costs.